Cash management practice, SACCO size and Kenya’s deposit taking saving and credit co-operatives financial sustainability - Justus Nderitu Maina; Richard Muthii Kiai; Teresia Ngina Kyalo (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
Deposit taking Savings and Credit Co-operatives (SACCO) are solution to social dilemmas like abject poverty, living standards and unemployment. Nevertheless, 14 percent do not maintain sound cash management practices despite SACCOs oversight authority in Kenya offering guidelines and supervision to the enterprises that would assist in maintaining their financial sustainability. This necessitated for the evaluation of the moderating effect of SACCO size on cash management practice and financial sustainability. A descriptive cross-sectional survey design with a positivism philosophical paradigm was adopted. Emailed questionnaire and data collection sheet were used in data collection which registered a 95 percent response rate. A binary logistic regression results established that with presence of a moderator for the predictor sub-variables, the strength of the relationship between variables registered an insignificant change but with introduction of interaction term, the strength of relationship between variables changed. The study concluded that SACCO size portrayed a statistically significant moderating effect on predictor sub-variables and response variable. The study thus recommends that the management need to consider increasing their SACCO sizes through merging, acquiring the non-performing SACCOs or even conducting intensive marketing since large size SACCO have low chances of being financially unsustainable